Factors associated with knowledge and vaccination intention for human papillomavirus on trans girls by their main caregiver: A cross-sectional study - Domínguez-Riscart, Jesus; Ariza-Jimenez, Ana-Belen; Baez-Castillo, Celia; Mateo-Gavira, Isabel (Frontiers in Immunology, 2023)
Introduction Trans women are highly affected by the human papillomavirus (HPV) and are at risk of suffering from HPV-related diseases such as oropharyngeal, anal, penile, or neovaginal neoplasia. HPV vaccination seems to be a good strategy to reduce HPV-related diseases, mainly during the early age before the first sexual intercourse, but only cisgender girls are covered by the National Health Services, while some high-risk groups such as trans girls are not included. Achieving a high vaccination rate is important in the adolescent population, but there are many factors that could affect it, such as lack of knowledge about HPV or fear of side effects by patients and main caregivers. The aim of our study is to analyze the knowledge of trans girls’ main caregivers about HPV-related diseases in the general population and, in particular, in trans women, as well as factors associated with HPV vaccination intention. Methods A cross-sectional study was performed with the collaboration of main caregivers of adolescent trans girls, between 9 and 16 years old, assisted in two reference centers’ multidisciplinary Gender Diversity Units. Information was requested through a self-completed questionnaire: HPV-related diseases Knowledge Transwomen questionnaire (HPV-TQ) was elaborated based on a 19-item self-administered questionnaire and score was standardized from 0 to 19 points. Percentage of correct answers was calculated and defined by the group of high scores that showed over 70% correct answers. Results A total of 65 main caregivers were included. Almost all main caregivers were mothers with a Caucasian ethnicity. The HPV-TQ average score was 11 (3.7) with an average correct answer of 58.1% (19.6). Only 17/65 (26.1%) of main caregivers were highly knowledgeable in HPV. Of 65 trans girls, 14 were already vaccinated (29.8% of trans girls over 12 years old); 78.5% were not vaccinated and only 21.5% had intentions to be vaccinated. The group with a high score in HPV-TQ had a longer follow-up at the transgender unit, a higher maternal vaccination rate, and a positive family history of HPV-related disease, especially in mothers. Conclusion Adolescent trans girls attended to in our units had a low rate and a low intention of vaccination against HPV. Education on and promotion and prevention of transgender HPV-related diseases should probably be implemented to achieve a higher knowledge and vaccination coverage in adolescent trans girls.